Meeting the challenges of climate change to tourism : case studies of best practice - D'Amore, Louis; Kalifungwa, Patrick (Cambridge Scholars Publishing, 2013)
As UN Secretary-General Ban Ki-moon has stated, ""Climate change is the pre-eminent geopolitical and economic issue of the 21st century. It rewrites the global equation for development, peace and prosperity."" The scientific evidence is clear - climate change is happening and the exposure to weather-related disasters such as heat waves, forest fires, cyclones and flooding has the potential to seriously impact the tourism sector. The travel and tourism industry is both a significant contributor ...